Identity Theft and the Dark Web: New Frontiers of the Criminal Activities - Dahiya, Nidhi; Harshita Bhardwaj (Journal of Advanced Research in Journalism & Mass Communication, 2025)
Identity theft has emerged as a pervasive and increasingly complex crime, significantly amplified by the dark web, a hidden and encrypted portion of the internet that offers anonymity and a decentralized platform to cybercriminal activities. This paper explores how the dark web has transformed traditional identity theft methods—such as phishing, hacking, and social engineering—by providing an environment where criminals can buy, sell, and trade stolen personal data, including debit/credit card information, credentials related to net banking, social security numbers (aadhaar card number), and medical records. The dark web’s encrypted nature and illicit activities, enabling criminals to operate with greater anonymity and evade law enforcement detection. The research delves into how the dark web facilitates the rapid exchange of stolen personal data, exacerbating the risks of financial fraud, impersonation, and other criminal behaviours. It highlights the challenges faced by law enforcement in tracking and prosecuting these crimes due to the anonymity provided by dark web marketplaces. Furthermore, it examines the broader implications of identity theft for cybersecurity, personal privacy, and criminal justice systems. The purpose of this study is to raise awareness about the growing threat posed by the dark web in the context of identity theft and to address the gaps in legal and cybersecurity measures. Finally, the study advocates for stronger preventative measures, including better surveillance, better awareness regarding the Information Security measure, more stringent regulations, and global collaboration, to protect personal information and adapt to the evolving landscape of cybercrime.